Kinetics of crystal violet dyes photocatalytic degradation in an aqueous media using TiO2 nanoparticles synthesized from Tithonia diversifolia leaf crude extracts - Samuel N. Ndung’u; Esther W. Kinuthia (Journal of Water and Environmental Nanotechnology)
The current study focused on the degradation of crystal violet (CV) dyes using TiO2 nanoparticles under UV light irradiation. The TiO2-NPs were biosynthesized using Tithonia diversifolia leaf crude extracts. They were then characterized using FT-IR, XRD, TGA, SEM-EDX, and UV-visible spectrophotometer and employed in dye photodegradation experiments. The T. diversifolia-mediated TiO2-NPs showed a maximum absorbance of 280 nm. The spectroscopic analysis showed thermally stable TiO2 nanoparticles dominated by the anatase phase with Ti-O-Ti and Ti-O functional groups. The nanoparticle efficiency (89.54 %) was greatly influenced by pH (9), interaction time (50 minutes), dosage (30 mg), and concentration (40 mg/L).  The kinetic plots indicated that the rate of CV photodegradation followed pseudo-first-order degradation mechanisms. The regeneration studies showed that the TiO2-NPs can be reused with a high degradation efficiency (> 60 %). The findings of the study report a novel, ecologically friendly, and cost-effective technique for TiO2-NPs synthesis for dye wastewater treatment.